Sharing untold insights on nutrition for public health: Knowledge forums on nutrition (Poshan Samvad) in Madhya Pradesh - Jain, Sachin Kumar; Dubey, Prashant; Agarwal, Meenakshi (International Food Policy Research Institute, 2014)
Poshan Samvad (hereinafter referred to as “the Knowledge Forum”) is a forum of and for frontline workers who are engaged in the domain of nutrition for public health. The Knowledge Forum is aimed at enabling these workers to come together to freely share and discuss among their peer and counterpart groups their ideas, perceptions, reflections, problems, prospects, issues, and concerns pertaining to the realities of combating malnutrition. The Forum is envisaged to go a long way toward responding to their questions and concerns. The consultations at the Forum will enhance and sustain the effectiveness of service providers by providing knowledgeable, articulated insights into the immediate and perturbing challenges they often confront toward achieving an informed resolution.